2006
DOI: 10.1111/j.1939-1676.2006.tb02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic VDD versus Nonphysiologic VVI Pacing in Canine 3rd‐Degree Atrioventricular Block

Abstract: Historically, ventricular demand, nonphysiologic (VVI) pacing has been the most commonly used modality to treat 3rd-degree atrioventricular (AV) block. The goal of this study was to determine the feasibility of using a commercial, single-lead, physiologic (VDD) pacemaker in dogs with 3rd-degree AV block. Furthermore, we hoped to characterize and identify differences in the radiographic, echocardiographic, neurohormonal, and quality of life consequences of physiologic versus nonphysiologic pacing. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…The prevalence of chronotropic incompetence in dogs with third-degree AVB is unknown. The potential for humans to develop sinus node disease after PM implantation is one argument against the utilization of a single lead physiologic PM [138]. In veterinary medicine, it has been described that dogs that present an atrial rate <70 beats per minute and a negative atropine response test (<25% increase of sinus rate 20e30 min post 0.04 mg/kg atropine SQ injection) [63] are excluded from consideration of single lead VDD PM implantation [110].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 99%
“…The prevalence of chronotropic incompetence in dogs with third-degree AVB is unknown. The potential for humans to develop sinus node disease after PM implantation is one argument against the utilization of a single lead physiologic PM [138]. In veterinary medicine, it has been described that dogs that present an atrial rate <70 beats per minute and a negative atropine response test (<25% increase of sinus rate 20e30 min post 0.04 mg/kg atropine SQ injection) [63] are excluded from consideration of single lead VDD PM implantation [110].…”
Section: Indications For Pacing and Choice Of Pacing Modementioning
confidence: 99%
“…In long‐term follow up studies the incidence of atrial fibrillation and pacemaker syndrome was significantly reduced 18 . In 1 study in dogs with AV block, VDD pacing was superior to VVI pacing as shown by an improvement in hemodynamic status and neurohormonal profiles 14 …”
mentioning
confidence: 98%
“…The alternative is the implantation of a single lead with a floating arterial electrode and VDD programming. Using the latter system, AV synchrony can be achieved, but there is no pacing in the right atrium 14 . In humans, dual chamber sequential pacing compared with VVI single chamber pacing improved cardiac output, blood pressure, exercise tolerance, and increased quality of life 15–17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sisson and others (1991), Oyama and others (2001), Wess and others (2006), Johnson and others (2007) and Hildebrandt and others (2009) used TTP in 10 per cent (four of 40), 46 per cent (69 of 154), 82 per cent (78 of 105), 50 per cent (52 of 104) and 24 per cent (eight of 33) of dogs that underwent PMI, respectively. There are also some reports on the use of TTP during PMI in single cases (Lombard and Buchanan 1976, Flanders and others 1999, Bulmer and others 2006, Saunders and others 2007). In addition, Darke and others (1989) attached temporary pacing leads to permanent pacing leads to perform external pacing.…”
Section: Discussionmentioning
confidence: 99%